Ciência nativa e arqueologia : uma análise interdisciplinar a partir da cartografia fluida dos Tabajara (PI) - Assis, Nívia Paula Dias de (2022)
In the present work, it was proposed to carry out an interdisciplinary study based on the identification of historical and territorial connections between the contemporary Tabajara village of Nazaré (PI) and the Tabajara who historically inhabited the Serra da Ibiapaba (CE-PI), considering that the self-identification of the first refers to the historical connection with the latter. The objective was to approach the history of the Tabajara from indigenous paradigms, using mainly the concept of native science and extending this analysis to issues of territorial mobility. Thus, from the information contained in the ethnographic map of Curt Nimuendajú, duly substantiated through historical and documentary research, data from archaeological research referring to Tupiguarani sites, located in the regional scope of the study area, were added and compared. With this, it was also possible to produce an “ethnocartography” aligned with this research. For this purpose, software tools specialized in geotechnology were used, developed for the calculation of possible paths of least effort during simulated distance displacements. The interdisciplinary results achieved, in turn, can bring contributions to studies directed to Indigenous History and Tupi Archeology, as well as to historical studies on indigenous territorialities.